Do urinary and double incontinence predict changes in living arrangements and mobility in older women after hip fracture? – a 1-year prospective cohort study - Hellman-Bronstein, Aino T. (BioMed Central Ltd, 2025)
Background: Continence problems are known to be associated with disability in older adults. Costs of disability and resulting need for more supported living arrangements are high after a hip fracture. The aim was to examine pre-fracture urinary incontinence (UI) and double incontinence (DI, concurrent UI and fecal incontinence) as predictors of changes in mobility and living arrangements in older female hip fracture patients in a 1-year follow-up.
Methods: Study population comprised 1,675 female patients aged ≥ 65 (mean age 82.7 ± 6.8) sustaining their first hip fracture between 2007-2019. Data on self-reported pre-fracture continence status was collected. The outcomes were declined vs. same or improved mobility level and need for more assisted vs same or less assisted living arrangements 1-year post-fracture. Separate cohorts of 1,226 and 1,055 women were generated for the mobility and living arrangements outcomes, respectively. Age- and multivariable-adjusted logistic regression models were used to determine the associations of UI, DI, and other baseline characteristics with the outcomes.
Results: Of the patients, 39% had declined mobility or more assisted living arrangements at 1-year follow-up. Adjusting for age, both pre-fracture UI and DI were associated with changes in mobility and living arrangements. In the multivariable analysis, UI (OR 1.88, 95% CI 1.41-2.51) and DI (1.99, 95% CI 1.21-3.27) were associated with decline in mobility level while only DI (OR 2.40, 95% CI 1.22-4.75) remained associated with the need for more assisted living arrangements.
Conclusions: Both pre-fracture UI and DI in older women are risk factors for declining mobility level, but only DI for more supported living arrangements 1-year post-hip fracture. UI likely develops earlier in life and might not necessarily be strongly associated with the onset or increasing disability in later years. DI may indicate more marked vulnerability and burden to patients as well as to formal and informal caregivers.